Discourse analysis of the representation of Hallaj's face in the works of Khwaja Abdullah Ansari - Mehrad Asad Paski; Ali Taslimi; Moamadkazem Yoosef Pour (ادبیات عرفانی)
Ansari is a prominent Sufi of the Sahv (school of soberness) and one of the famous Hanbali scholars. His life was dedicated to writing hadith, guidance and anti-innovation. Like Hojviri and Qosheiri, he expounded some topics of Sufism in his works, and in line with this aim, the views of Hallaj were also reflected in these works as one of the crucial elements of Sufism. The aim of the present article is to introduce these views.This research tries to study Hallaj's representation by combining the three-level discourse analysis methods of Fairclough, Laclou, and Mouffe.  In the description part, Halliday's systematized order was used, which is suitable for the study of verbs and processes. From the perspective of a Hanbali Shaykh-al-Islam, the survey results show that everything related to observing the limits of the Sharia Law in the words of Hallaj is acceptable to Ansari, and not adhering to the appearances of the Sharia Law is not acceptable to him. However, he did not believe that Hallaj deserved an unfortunate end. From the perspective of Sufi discourse, he shares a similar viewpoint with other Sufis from the Sahv School of Thought towards Hallaj. sincere in his relationship with God (Sir-El-Allah) and disapproves of revealing the secrets of Sufism to the general public, considering it a form of ingratitude toward the master. He believes that Hallaj’s tragic fate resulted from this ingratitude.